Management and epidemiology of Cytospora perennial canker, Cytospora plurivora, in western Colorado - Miller, Stephan T., author; Stewart, Jane, advisor; Ocheltree, Troy, committee member; Norton, Andrew, committee member; Minas, Ioannis, committee member; Uchanski, Mark, committee member (Colorado State University. Libraries, 2021)
Cytospora canker is a ubiquitous disease in deciduous fruit tree systems in western Colorado. The research conducted herein, explores the host-pathogen-environmental framework which has enabled Cytospora plurivora to thrive and become a threat to peach production in the region. My research also focuses on management strategies, both cultural and chemical, which can help mitigate pathogen infections. Chapter II, published in the Journal of Crop Protection, presents preventative control of C. plurivora through wound protection of pruned shoots. Several fungicides and sealants were evaluated either in vitro or in field trials, to explore antifungal activity. Fungicides which have been shown effective, were also evaluated for half maximum effective concentration rates (EC50) to better understand pathogen dose sensitivity. Chapter III explores the susceptibility of thirteen peach cultivars to C. plurivora infection under different abiotic conditions. Abiotic stressors such as water deficit and high-pH can be major limiting factors to tree fruit production and can increase tree susceptibility and pathogen severity. My research shows increased severity of C. plurivora infection and decreased plant water potentials when trees experienced increased soil pH and irrigation deficits. Chapter IV provides a detailed analysis of the epidemiology of C. plurivora in the field. This study estimates spore production rates and lesion infection rates over a 12-month period. Further, it evaluates possible dissemination mechanisms of C. plurivora, reporting detection of C. plurivora spores in aerial and on insect samples, although at low concentrations. The results presented herein help inform management strategies by elucidating field patterns of C. plurivora and identifying effective cultural and chemical control measures.